Efektivitas Penggunaan Aplikasi Berbasis Teknologi dalam Meningkatkan Kreativitas Siswa dalam Menulis Teks Cerpen di Kelas IX-9 SMP Negeri 8 Medan - Sembiring, Elsana; Ali, Ali; Evita, Evita (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2025)
This study investigates the effectiveness of integrating technology-based applications in enhancing students’ creativity in writing short story texts among ninth-grade students at SMP Negeri 8 Medan. Employing a Classroom Action Research (CAR) approach based on the Kemmis and McTaggart model, the research was conducted in four iterative phases: planning, implementation, observation, and reflection. The participants comprised 30 students from Class IX-9. Data were collected through observations, questionnaires, interviews, and writing skill assessments via pre-tests and post-tests. Both quantitative and qualitative analyses were employed to assess changes in students’ creative writing abilities. The findings demonstrate a substantial improvement: the pre-test average score was 68.5 with a classical completeness of 60%, while the post-test average rose to 82.3 with 86.7% completeness. Qualitative data further revealed increased student motivation and engagement during writing activities. Teachers reported that the technology-based tools effectively stimulated students' imagination and helped them produce more compelling narratives. The study concludes that incorporating technology into short story writing instruction significantly fosters students’ creativity and recommends its broader application as an innovative pedagogical strategy in language learning.